Examining Job Hopping among Gen Z in Bandar Lampung: Is It Really Driven by Work-Life Balance and Job Satisfaction? - Siti Nurhasanah; Jeni Wulandari; Fenny Saptiani (Cita konsultindo, 2025)
The phenomenon of job hopping among Gen Z is becoming increasingly prevalent, particularly in developing cities such as Bandar Lampung. This generation is known for having high expectations regarding work life balance and job satisfaction, which can influence their decision to stay or switch jobs. This study aims to analyse the impact of work life balance and job satisfaction on the job-hopping intentions of Gen Z employees in Bandar Lampung. This research employs an explanatory research method with a quantitative approach. The sample consists of 385 respondents aged 18–29 years in 2024, selected using a purposive sampling technique. Data were collected through a digital questionnaire (Google Forms) and measured using a Likert scale with a negative model. Data analysis was conducted using the SPSS statistical software. The results indicate that, partially, work life balance has a significant positive effect on job-hopping intentions, as does job satisfaction, which also significantly influences job-hopping intentions. Simultaneously, both variables have a significant impact on Gen Z employees' decisions to change jobs. These findings provide insights for companies to better understand Gen Z's mindset in the workplace by creating a work environment that supports both work life balance and job satisfaction, aligning with the preferences of Gen Z employees.